JavaFX : a beginner's guide - DiMarzio, J. F. (New York : McGraw-Hill, 2011)
'Create immersive, interactive environments for any platform. JavaFXTM: A Beginner's Guide begins by explaining the technology behind JavaFX and quickly moves on to installing the JavaFX development environment and tools, including the JavaFX SDK, the Java SE JDK, and NetBeans. Then, you'll learn how to develop desktop, browser, and mobile applications with ease. The book covers effects and transformations, animation, events, and Swing components. Techniques for creating custom nodes, embedding video and music, using JavaFX layouts, and styling with CSS are also discussed'--
Introduction to JavaFX -- Setting the scene -- Hello world -- Creating shapes -- Using colors and gradients -- Using images -- Applying effects and transformations -- Basic animation -- Using events -- Give it some swing -- Custom nodes and overriding -- Embedded video and music -- Using JavaFX layouts -- Style your JavaFX with CSS -- Deploying JavaFX -- Node property reference -- JavaFX command-line arguments -- Answers to self tests.
'Covers release 1.3'--Cover.
Includes index.
Keywords: JavaFX (Electronic resource); Java (Computer program language); Graphical user interfaces (Computer systems)